Upregulation of insulin secretion and downregulation of pro-inflammatory cytokines, oxidative stress and hyperglycemia in STZ-nicotinamide-induced type 2 diabetic rats by Pseuduvaria monticola bark extract - Taha, H.; Arya, Aditya; Paydar, M.; Looi, Chung Yeng; Wong, Won Fen; Murthy, C.R.V.; Noordin, M.I.; Ali, Hapipah Mohd; Mustafa, A.M.; Hadi, A.H.A. (Elsevier, 2014)
The current study aimed to ascertain the antidiabetic potential of Pseuduvaria monticola bark methanolic extract (PMm) using in vitro mechanistic study models. In particular, the study determined the effect of PMm on cellular viability, 2-NBDG glucose uptake, insulin secretion, and NF-jB translocation in mouse pancreatic insulinoma cells (NIT-1). Furthermore, in vivo acute toxicity and antidiabetic studies were performed using streptozotocin (STZ)-induced type 1 and STZ-nicotinamide-induced type 2 diabetic rat models to evaluate various biochemical parameters and markers of oxidative stress and pro-inflammatory cytokines. Five isoquinoline alkaloids and three phenolic compounds were tentatively identified in the PMm by LC/MS Triple TOF. The study results showed that PMm is non-toxic to NIT-1 cells and significantly increased the glucose uptake and insulin secretion without affecting the translocation of NF-jB. Moreover, the non-toxic effects of PMm were confirmed through an in vivo acute toxicity study, which revealed that the serum insulin and C-peptide levels were significantly upregulated in type 2 diabetic rats and that no significant changes were observed in type 1 diabetic rats. Similarly, PMm was found to downregulate the levels of oxidative stress and pro-inflammatory cytokines in type 2 diabetic rats by alleviating hyperglycemia. Therefore, we conclude that PMm may be developed as an antidiabetic agent for the treatment of type 2 diabetes-associated conditions.